The Role of Multiculturalism in Supporting Economic Development and Local Identity in Brebes Regency - Diah Nadiatul Jannah (Research Agency for Humanity and Urban, 2026)
This study aims to analyze the role of multiculturalism in supporting economic development and local identity in Brebes Regency. The study employed a literature review method with a descriptive qualitative approach through data collection from journals, books, government documents, and other relevant references. The results show that the cultural diversity of Brebes society, particularly the interaction between Javanese and Sundanese cultures, plays an important role in forming social capital that supports community economic activities. In addition, local identities such as shallots and Brebes salted eggs have developed as cultural symbols and regional economic strengths through SMEs, trade, and the creative economy. However, globalization and modernization pose challenges to the sustainability of local culture. Therefore, strengthening local culture and developing culture-based creative economy are necessary to support sustainable regional development.